Cyclic nitrones: oxidation studies and the synthesis of a heterocyclic nitrone - Elsworth, John Francis (Department of Chemistry, 2017)
Part I: The synthesis of the heterocyclic nitrone, Δ³-dihydro-1,4-oxazine 4-oxide, by the oxidation of solutions of 4-hydroxymorpholine is described. The UV and IR spectra of the solutions were consistent with the structure proposed. Removal of the solvent gave linear polymers with the N-O-C repeating unit. Typical nitrone-reducing agents have been shown to be effective towards the heterocyclic nitrone. Arylhydrazines oxidised the heterocyclic nitrone with cleavage of the ether band, yielding glyoxal osazones. The same nitrone was very rapidly oxidised to 4-hydroxy-3-morpholone by ferric chloride. This cyclic hydroxamic acid underwent further oxidation at a slower rate, ultimately yielding diglycollic acid and nitrous oxide. 1,3-Cycloaddition products were formed when the heterocyclic nitrone was heated together with cyclohexene, with phenylisocyanate and with ethyl acrylate. All the products incorporated the fused bicyclic skeleton of morpholino-isoxazolidine and were each characterised by analysis, IR and p.m.r. spectra. Part 2: Cyclic aldonitrones and some related cyclic hydroxylamines have been shown to undergo oxidation by ferric chloride to cyclic hydroxamic acids. For example, the 2-unsubstituted 1-pyrroline 1-oxides gave l-hydroxy-2-pyrrolidones , and 1-piperideine 1-oxide gave 1-hydroxy-2-piperidone. The reaction could be followed titrimetrically or spectrophotometrically. The former involved the determination of the ferrous ion released, whereas the latter technique entailed observing the increase in the intensity of the colour of the solution.